2017
DOI: 10.1177/1687814017700829
|View full text |Cite
|
Sign up to set email alerts
|

An integrated control method for designing non-blocking supervisors using Petri nets

Abstract: This article presents an efficient integrated approach on designing a non-blocking supervisor for the most general classes of Petri nets, called G-systems that allow multiple resource acquisitions. This work mainly focuses on developing a deadlock prevention policy with a polynomial computational complexity. First, an extraction algorithm of liveness requirement constraints is presented according to the concept of resource partial orders. By considering the different resource requirements of various processes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…The everincreasing complexity of the PLC software and user-imposed operational and security specifications require new techniques to meet the control requirements. Petri nets (PNs) are a very interesting and useful graphical and mathematical tool for the modeling and control of manufacturing systems [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Indeed, PNs have advantages over other languages, including simple graphical representation (circles, rectangles, and arcs), structured algorithms, and simple algebraic representation [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The everincreasing complexity of the PLC software and user-imposed operational and security specifications require new techniques to meet the control requirements. Petri nets (PNs) are a very interesting and useful graphical and mathematical tool for the modeling and control of manufacturing systems [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Indeed, PNs have advantages over other languages, including simple graphical representation (circles, rectangles, and arcs), structured algorithms, and simple algebraic representation [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, many investigations focus on deadlock control in FMSs. [1][2][3][4][5] Due to their appealing formal and graphical representation, Petri nets (PNs) are extensively adopted for modeling, analysis, scheduling, [6][7][8][9] and supervisory control [10][11][12] and hence adopted for handling the deadlock problems in FMSs. A seminal work in Zhou and Dicesare 13 contributes a PN model synthesis method for FMSs, where the places in a PN that are modeling of an FMS are first classified to A-, B-, and C-places.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the approaches in Chen et al 24 cannot deal with a large-scale systems with a large initial marking due to the state explosion problem. 25 The works in Zhao 4 provide a deadlock control policy based on the divide-and-conquer strategy. However, the method in Zhao 4 has a high computational complexity since it needs to handle a large number of subsystems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed strategy can also improve the utilization rate of the available loads. The third article, authored by Zhao, 11 aims to design a supervisor for a production system where an operation may have multiple resource acquisition requirements such that the system is blocking-free. A two-stage method is proposed to synthesize a blocking-free supervisor and it is shown that such a supervisor with simple controller structure can be efficiently designed.…”
mentioning
confidence: 99%